August Snow - Jones, Stephen Mack (Soho Crime, 2017)
"Tough, smart, and struggling to stay afloat, August Snow is the embodiment of Detroit. The son of an African American father and a Mexican mother, August grew up in Detroit's Mexicantown and joined the Detroit police only to be drummed out of the force by a conspiracy of corrupt cops and politicians. But August fought back; he took on the city and got himself a $12 million wrongful dismissal settlement that left him low on friends. He has just returned to the house he grew up in after a year away and quickly learns he has many scores to settle. It's not long before he's summoned to the palatial Grosse Point Estates home of business magnate Eleanore Paget. Powerful and manipulative, Paget wants August to investigate the increasingly unusual happenings ather private wealth management bank. But detective work is no longer August's beat, and he declines. A day later, Paget is dead of an apparent suicide--which August isn't buying for a minute. What begins as an inquiry into Eleanore Paget's death soon drags August into a rat's nest of Detroit's most dangerous criminals, from corporate embezzlers to tattooed mercenaries. From the wealthy suburbs to the near-post-apocalyptic remains of the bankrupt city's factory districts, August Snow is a fast-paced tale of murder, greed, sex, economic cyber-terrorism, race and urban decay in modern Detroit"--